THE EFFECT OF STORAGE TIME AND TYPE OF ANTIKOAGULANT IN PLATELET RICH PLASMA (PRP) ON PLATELET COUNTS - Lestari, Felia; Noviar, Ganjar; Nurhayati, Betty; Hayati, Eem (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2024)
Background: Platelet Rich Plasma is a biological product in the form of autologous plasma produced from the centrifugation process of blood specimens and has a platelet concentration above normal values. Things that can affect the results of PRP are blood collection, centrifugation speed, centrifugation time and temperature and the use of anticoagulants. Aims: The purpose of this study was to determine the average and see the effect of sodium citrate anticoagulant and ACD-A anticoagulant by using a shelf life of 0 hours, 4 hours and 8 hours in PRP on platelet count. Methods: This type of research is a pseudo-experiment with a Statistica Group Comparison research design. The number of samples in this study were 6 people. PRP research data on platelet count was processed statistically with the General Linear Model (GLM) method. The Results: The average data of PRP on platelet count using sodium citrate anticoagulant with a shelf life of 0 hours 533.333 cell/µL; 4 hours 527.167 cell/µL; 8 hours 190.167 cell/µL. Average data of PRP on platelet count using ACD-A anticoagulant with a shelf life of 0 hours 986.333 cell/µL; 4 hours 976.500 cell/µL; 8 hours 634.833 cell/µL. The data results for 0 hour and 4 hour shelf life on anticoagulants Sodium Citrate and ACD-A have a Sig value of 0.646 0.05 while 8 hour shelf life has a Sig value of 0.000 0.05. Conclusion: No effect of 0 hour and 4 hour shelf life while there is an effect of 8 hour shelf life and there is an effect of anticoagulants Sodium Citrate and ACD-A in PRP on platelet count.